2022
DOI: 10.1136/bmjqs-2021-013785
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising Responses Of Nurses To deteriorating patient Observations (PRONTO): a pragmatic cluster randomised controlled trial evaluating the effectiveness of a facilitation intervention on recognition and response to clinical deterioration

Abstract: BackgroundMost hospitals use physiological signs to trigger an urgent clinical review. We investigated whether facilitation could improve nurses’ vital sign measurement, interpretation, treatment and escalation of care for deteriorating patients.MethodsIn a pragmatic cluster randomised controlled trial, we randomised 36 inpatient wards at four acute hospitals to receive standard clinical practice guideline (CPG) dissemination to ward staff (n=18) or facilitated implementation for 6 months following standard di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…• Nurses engage in a range of nursing interventions to manage deteriorating patients (aside from rapid response system activation) that are not well understood, nor well described in the literature to date. randomised controlled trial that tested the effect of a facilitation intervention on nurses' vital sign measurement, interpretation, and escalation of care for deteriorating patients (Bucknall et al, 2022).…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
See 2 more Smart Citations
“…• Nurses engage in a range of nursing interventions to manage deteriorating patients (aside from rapid response system activation) that are not well understood, nor well described in the literature to date. randomised controlled trial that tested the effect of a facilitation intervention on nurses' vital sign measurement, interpretation, and escalation of care for deteriorating patients (Bucknall et al, 2022).…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
“…The outcomes of interest were as follows: (i) vital sign assessments at least 8-hourly on every patient; (ii) escalation of care per policy for patients with vital sign abnormalities; and (iii) implemen- Managers at staff meetings and via email, and notification of free online educational courses about recognition and response to deteriorating patients (Bucknall et al, 2017). The intervention wards (n = 18) had an external facilitator across hospitals, an internal hospital facilitator (HFLIP) and two ward facilitators (WFLIPs) per ward for 6 months who used facilitation methods to address barriers and leverage enablers to achieve the desired outcomes (Bucknall et al, 2022). There were no significant differences in any of the three outcomes of interest between intervention and control wards at 6 or 12 months post-intervention (Bucknall et al, 2022).…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that signs of clinical deterioration, such as abnormal heart rate, respiratory rate, or oxygen saturation can occur several hours before serious adverse events [11,12]. Therefore, earlier recognition of deterioration and escalation is crucial for ward nurses to gain time to stabilize patients and perhaps mitigate serious adverse events [13,14]. Several machine-learning algorithms have been developed to support staff in identifying patterns which can predict patients who may deteriorate in the future [10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The Prioritising Responses of Nurses to deteriorating patient Observations (PRONTO) trial reported in this issue of BMJ Quality and Safety describes results of a trial that overall, despite a few positive findings among the large number of planned comparisons performed, produced results that supported rather than rejected the study null hypotheses 1. This is a disappointing result for the investigators, who put considerable time and energy into this study; for funders, who hoped to learn how to positively influence the quality and safety of nursing care for seriously ill adults; and for readers, who also hoped to learn how to influence and support high-quality care by ensuring that nurses activate support systems in response to patient deterioration in hospitals.…”
mentioning
confidence: 99%